CPW-fed third iterative square-shaped fractal antenna for UWB applications - Pandey A.; Singhal S.; Singh A.K. (My University, 2025)
A CPW-fed square shaped fractal antenna for ultrawideband applications is presented. The bandwidth is enhanced using three iterations of square radiating patch, modified feed line, and rectangular notch-loaded ground plane. The designed antenna structure has an impedance bandwidth of 3.4-15 GHz along with omnidirectional radiation patterns in the entire operating band with an average gain of 4 dB. A good agreement between the simulation and experimental results is observed. The designed antenna structure has advantages of miniaturized size and wider bandwidth in comparison to previously reported structures. © 2016 Wiley Periodicals, Inc.